2004
DOI: 10.1007/s00408-003-1041-y
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Lavage with Lidocaine Improves Pulmonary Function in Piglets after HCl-Induced Acute Lung Injury

Abstract: Acute respiratory distress syndrome (ARDS) is associated with significant morbidity and mortality. The pathophysiology of ARDS includes abnormalities of surfactant function as well as pulmonary inflammation. Immunomodulating drugs, like Lidocaine, have shown some success in decreasing inflammation in ARDS. We attempted to combine surfactant lavage's ability to reverse the surfactant dysfunction, while acting as a vehicle to deliver Lidocaine. Gravity-driven surfactant (Infasurf) lavage (35 ml/kg) was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
9
0
3
Order By: Relevance
“…26,27,29,31 Although the lavage method is preferred in most studies, there are differences in terms of the volume of lavage (5 to 35 ml/kg), active vs passive instillation and fluid recovery, and number of lavages performed. 5,6,17,28,30,[32][33][34] Despite these differences, all studies reported improved lung function after dilute surfactant administration.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…26,27,29,31 Although the lavage method is preferred in most studies, there are differences in terms of the volume of lavage (5 to 35 ml/kg), active vs passive instillation and fluid recovery, and number of lavages performed. 5,6,17,28,30,[32][33][34] Despite these differences, all studies reported improved lung function after dilute surfactant administration.…”
mentioning
confidence: 76%
“…The ex vivo lung perfusion method has been proposed originally to assess the function of the lung from a non-heart-beating donor as an interim evaluation of the graft prior to transplantation. 17,18 Recently, Steen et al successfully reconditioned a rejected donor lung due to bilateral pulmonary contusion using an ex vivo perfusion system. 19 We showed that graft function improved with dilute surfactant lavage after high-volume aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of ventilatory maneuvers are employed to combat it, such as mechanical ventilation with prone and/or supine position, positive end expiratory pressure (PEEP), alveolar recruitment, high-frequency ventilation and non-ventilatory maneuvers such as the administration of nitric oxide and surfactant, fluids management, corticoids [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Para o seu combate, utilizam-se várias manobras ventilatórias, como a ventilação mecânica com pressão expiratória positiva final (PEEP), recrutamento alveolar, ventilação de alta freqüência [3][4][5] e manobras não-ventilatórias, como a administração de óxido nítrico, surfactante, balanço hídrico, uso de corticóides [5][6][7][8] , etc.…”
Section: Introductionunclassified